Formulating business strategy using strategy diamond, case study : rumah makan bu haji cibubur - Nindya Basuki, Karisha; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract - Rumah Makan Bu Haji Cibubur is a traditional restaurant that has been established in Cibubur since 1995. Its consistency on providing authentic traditional taste food with quick serving service has made it this far. This restaurant was having first mover advantage on providing customized soto betawi. Today, food industry in Cibubur has growth rapidly. This interesting growth of food industry had become a challenging market as there are increased of number competitors (direct and subtitutes) as well. In order to grow, compete, and sustain in this challenging market, Rumah Makan Bu Haji Cibubur needs to find its competitive advantage through optimizing its asset. Internal and external environment analysis is done to formulate business strategy using strategy diamond. Strategy diamond is a framework comprising five facets for understanding the content of a strategy (arena, vehicle, differentiator, staging, and economic logic). In proposed arena, maintaining major cluster of customers are important, but targeting new potential market is an opportunity to expand the market. By enhancing current differentiators, this restaurant could create a bigger value that will help to boost sales of goods and services as well as increase in profit. Implementation plan is done in staging in order to keep the development alligned. Pricing over value analysis is done to support economic logic. The conclusion of this research are focussing on its internal development. Through optimizing assets and infrastructure, Rumah Makan Bu Haji Cibubur will strengthened its internal management to prepare for a bigger challenge in the future. The recommendations  involves various internal development from conducting research, sales promotion, enhancing products and services as well as creating joint venture to support delivery services. All the proposed business strategy and recommendation will still hold its ‘authentic’ image. Keywords : Business Strategy, Strategy Diamond, AHP, Traditional Restaurant.